Incubator Analyzer Using Bluetooth Android Display (Humidity & Air Flow) - Vina Nadhirotul Azkiyak; Syaifudin Syaifudin; Dyah Titisari (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Abstract— Incubator Analyzer is a calibrator used to calibrate incubator temperature, mattress temperature, noise, humidity and airflow so that conditions in the baby incubator environment remain stable and within normal limits. The purpose of this study is to develop a system for sending data to android and data storage. "Incubator Analyzer Using Bluetooth Appear Android" has four parameters for measuring temperature, noise, humidity, and water flow. Using the Atmega328 microcontroller as a data processor, and the output results will be displayed on the LCD display and equipped with data transmission via bluetooth HC-05 displayed to Android with data storage. The moisture parameter detects humidity quite well where the biggest error is obtained at 1.28% DHT-22, the Ultrasound Sensor HC SR-04 can detect Air Flow with an error of 311.66% as measured by a comparison device. Incubator Design This analyzer is made portable to calibrate baby incubator tools.